Innovation Needs, Social Capital, and Learning Process of Batik Craftsmen - Entoh Tohani; Sugito Sugito (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2019)
AbstractThis study aims to determine batik craftsmen‘s innovation needs and learning process in relation to ownership of social capital. This study is stimulated by an assumption explaining that batik craftsmen’s are able to fulfill their innovation needs through learning process by utilizing established social capital in the batik production context. This qualitative research was conducted on three batik craft SMEs in two sub-districts in Bantul Regency, the center of Yogyakarta's batik production. The research subjects were craftsmen, workers, batik organizers, and community leaders. Data collection is conducted through observation and in-depth interviews. Meanwhile the data were analyzed by using qualitative analysis techniques. The research result reveals that the SMEs of batik craftsmen have diverse innovation needs in expanding their business. Moreover, to fulfill their innovation needs, they also conducted both independent and cooperative learning by utilizing the existing social capital. Yet, the learning process has not been optimally conducted. Thus, empowerment efforts are necessary to develop learning skills by utilizing social capital to meet craftsmen’s innovation needs. Keywords: social capital, learning process, innovation, batik, needsKebutuhan Inovasi, Modal Sosial, dan Proses Belajar Perajin BatikAbstrakPenelitian ini bertujuan untuk mengetahui kebutuhan inovasi dan proses belajar para perajin batik dalam konteks kepemilikan modal sosial. Hal ini didasarkan pada pandangan bahwa kebutuhan inovasi dapat dipenuhi apabila para perajin dapat memanfaatkan modal sosial yang terbangun dalam konteks usaha produksi batik melalui proses belajar yang mungkin terjadi di dalamnya. Penelitian kualitatif ini dilakukan terhadap tiga UKM perajin batik di dua kecamatan di Kabupaten Bantul sebagai sentra produksi batik Yogyakarta. Subjek penelitian adalah para perajin, pekerja, pengurus paguyuban batik, dan tokoh masyarakat. Pengumpulan data dengan observasi dan wawancara mendalam dan data dianalisis menggunakan teknik analisis kualitatif. Hasil penelitian menunjukkan bahwa perajin batik memiliki kebutuhan inovasi yang beragam dalam mengembangkan usahanya dan melakukan proses belajar baik secara mandiri maupun kooperatif dengan memanfaatkan modal sosial sebagai hasil interaksi dengan lingkungannya guna memenuhi kebutuhan inovasinya walaupun belum optimal. Oleh karena itu, diperlukan tindakan-tindakan pemberdayaan untuk meningkatkan kemampuan belajar dengan memanfaatkan modal sosial guna memenuhi kebutuhan inovasi perajin. Kata kunci: modal sosial, proses belajar, inovasi, batik, kebutuhan